Sri Lanka : Staff Report for the 2005 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
Sri Lanka's 2005 Article IV Consultation reports that the fiscal deficit exceeded budget targets, and with a significant amount of government financing provided by the central bank, the growth in monetary aggregates increased, contributing to higher inflation. The near-term economic outlook is to a large extent shaped by the post-tsunami reconstruction effort. Reconstruction and a quick rebound in tourism should maintain growth momentum, but demand pressures and fuel price adjustments are expected to keep inflation in double digits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet